Evaluasi Program Praktik Kerja Lapangan Integratif Fakultas Tarbiyah UIN Maliki Malang - Ali, Nur (Fakultas Ilmu Tarbiyah dan Keguruan Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2013)
Faculty of Tarbiyah and Teaching Training Maulana Malik Ibrahim State Islamic University Malang as Educational institute of teacher training has participatedin educating the students to be a professional teachers atelementary, junior and senior high schools. One of the way to realize it is through conducting teaching practicum in micro-teaching atcampus and integrated teaching practicum program at madrasah and schools.This research isto know how was the guidance teachers and principals of madrasahs and schools towards the competences of students in conducting integrated teaching practicum program at madrasah and schools. It used survey design because it was inflenced by the development of socials and eduational policy.The results of this research showed that the evaluation of guidance teachers and principals of madrasahs and schoolstowards the competences of the students in conducting integrated teaching practicum program at madrasah and schools was good.Keywords: profesional, personal, dan social competence.